(untitled) (Revista Cocar, 2019)
Presentation of the Dossier Apresentação pelas organizadoras do Dossiê: crianças, mídias e mediações dos objetivos e temas dos artigos que constituem o Dossiê. Presentation by the organizers of the Dossier: children, media and mediations of the objectives and themes of the articles that make up the Dossier.